2018
DOI: 10.1002/fsn3.753
|View full text |Cite
|
Sign up to set email alerts
|

Partial‐least‐squares and canonical‐correlation analysis of chemical constituents and active ingredients of new types of Chinese mulberries

Abstract: ObjectiveTo investigate the correlation between chemical constituents and active ingredients of 13 types of Chinese mulberry fruits.MethodsThirteen types mulberry fruits were harvested. The correlation between chemical constituents and active ingredients (primarily anthocyanins and rutins) of 13 new types of Chinese mulberries was assessed using partial‐least‐squares, principle‐component and canonical‐correlation analyses.ResultsVitamin C and titratable acid in the mulberry fruits were critical components that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 34 publications
4
9
0
Order By: Relevance
“…Principal component analysis concerns a mathematical procedure that transforms a number of possibly correlated variables into a smaller number of uncorrelated variables (Huang et al., 2020; Zhao, Chang, & Chen, 2015). PCA provides visual patterns (Castro‐Alba et al., 2019; Chen, Sun, & Ford, 2014; Reale et al., 2020; Sun, Sun, & Han, 2018) which can be understood and accepted easily; furthermore, the results also avoid subjective decisions. In the present study, to assess the resemblance and differences between wild and cultivated samples, a PCA was performed based on the eight common peaks (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Principal component analysis concerns a mathematical procedure that transforms a number of possibly correlated variables into a smaller number of uncorrelated variables (Huang et al., 2020; Zhao, Chang, & Chen, 2015). PCA provides visual patterns (Castro‐Alba et al., 2019; Chen, Sun, & Ford, 2014; Reale et al., 2020; Sun, Sun, & Han, 2018) which can be understood and accepted easily; furthermore, the results also avoid subjective decisions. In the present study, to assess the resemblance and differences between wild and cultivated samples, a PCA was performed based on the eight common peaks (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The average contents of the trace element components in the mulberry fruits are shown in Table 2 . DM can range from 9.45% to 28.50%, CP can vary from 0.51% to 12.98%, fat can vary from 0.34% to 7.21%, CF can vary from 0.57% to 14.0%, ash can vary from 0.46% to 4.79%, and carb can vary from 13.83% to 71.7% [ 20 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. A study by Imran et al [ 41 ] showed that the GE in the mulberry fruit can range from 67.36 to 84.22 kcal/100 g.…”
Section: Nutrients Derived From the Mulberry Tree And Its Extractsmentioning
confidence: 99%
“…Additionally, the mulberry fruit also contains Fe (1.17–77.6 mg/100 g), Zn (0.14–59.20 mg/100 g), Ca (38.89–576 mg/100 g), magnesium (Mg, 12.21–360 mg/100 g), kalium (K, 87.70–2170 mg/100 g), sodium (Na, 5.9–280 mg/100 g), manganese (Mn, 0.03–4.36 mg/100 g), and copper (Cu, 0.04–1.31%) [ 20 , 40 , 41 , 42 , 43 , 46 , 47 , 48 , 49 ]. Ascorbic acid ranges from 15.20 to 22.4 mg/100 g [ 20 , 41 ]…”
Section: Nutrients Derived From the Mulberry Tree And Its Extractsmentioning
confidence: 99%
“…Mulberry is an important source of mineral elements, in particular, potassium and, to a lesser extent, calcium [ 17 , 18 ]. Sun et al concluded that mineral element content interacted with sugar, crude protein, crude fat, and pectin content [ 19 ]. In particular, its black berries contain very important chemical substances with high anthocyanin contents and antioxidant activities, which are useful for the increases in primary agricultural production, the food industry, and the prevention and treatment of human diseases [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%